2014
DOI: 10.3390/geosciences4030114
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax and the Geochemistry of Soils in the Contiguous United States

Abstract: Soil geochemical data from sample sites in counties that reported occurrences of anthrax in wildlife and livestock since 2000 were evaluated against counties within the same states (MN, MT, ND, NV, OR, SD and TX) that did not report occurrences. These data identified the elements, calcium (Ca), manganese (Mn), phosphorus (P) and strontium (Sr), as having statistically significant differences in concentrations between county type (anthrax occurrence versus no occurrence). Tentative threshold values of the lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Furthermore, 1-km grid soil type and soil pH data obtained from the ISRIC African soil database were also included; soil pH was included as a predictor variable because it has been shown that epidemics of anthrax are associated with an alkaline pH (Dragon and Rennie, 1995). Soil type as a categorical variable was also included in the model, because the influence of soil type on B. anthracis spores persistence is ecologically documented and it is speculated that there is a significant relationship between the soil type and the extensive presence of anthrax outbreaks in certain areas (Griffin et al, 2014).…”
Section: Environmental Covariatesmentioning
confidence: 99%
“…Furthermore, 1-km grid soil type and soil pH data obtained from the ISRIC African soil database were also included; soil pH was included as a predictor variable because it has been shown that epidemics of anthrax are associated with an alkaline pH (Dragon and Rennie, 1995). Soil type as a categorical variable was also included in the model, because the influence of soil type on B. anthracis spores persistence is ecologically documented and it is speculated that there is a significant relationship between the soil type and the extensive presence of anthrax outbreaks in certain areas (Griffin et al, 2014).…”
Section: Environmental Covariatesmentioning
confidence: 99%
“…In this setup, anthrax outbreaks have been reported in livestock butnone in wildlife in adjacent Hwange NP up to 2018. This suggests that either the disease was occurring in Hwange NP wildlife but being missed due to sub-optimal surveillance [ 40 ] as ascertained by the principal researcher on area visit (September, 2015), or that it was truly absent due to environmental influences [ 41 , 42 ]. Even though Chikerema et al .…”
Section: Discussionmentioning
confidence: 99%
“…The causative agent of the disease, Bacillus anthracis, is a soil-borne bacterium with a remarkable ability to survive in the environment for long periods of time (Hugh-Jones & Blackburn, 2009). Studies have shown that the geographic distribution of the bacterium is limited by a combination of environmental characteristics including soil pH, several soil minerals, soil moisture, and temperature (Blackburn, McNyset, Curtis, & Hugh-Jones, 2007;Griffin, Petrosky, Morman, & Luna, 2009;Griffin et al, 2014;Hugh-Jones & Blackburn, 2009;Kracalik et al, 2012;Smith et al, 2000). Human transmission of anthrax is generally a direct result of coming into contact with infected animals or contaminated materials, hence control of the disease in humans is dependent upon targeting control efforts in animals.…”
Section: Introductionmentioning
confidence: 96%